2013
DOI: 10.1063/1.4808379
|View full text |Cite
|
Sign up to set email alerts
|

Large-area microfocal spectroscopic ellipsometry mapping of thickness and electronic properties of epitaxial graphene on Si- and C-face of 3C-SiC(111)

Abstract: Microfocal spectroscopic ellipsometry mapping of the electronic properties and thickness of epitaxial graphene grown by high-temperature sublimation on 3C-SiC (111) substrates is reported. Growth of one monolayer graphene is demonstrated on both Si- and C-polarity of the 3C-SiC substrates and it is shown that large area homogeneous single monolayer graphene can be achieved on the Si-face substrates. Correlations between the number of graphene monolayers on one hand and the main transition associated with an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…It is known as the buffer layer or zero-layer graphene [25,40,89,[92][93][94]. This reconstructed surface loses its distinct graphene electronic properties because of sp 3 hybridization of about 30% of the carbon atoms which are covalently bonded with the Si atoms of the SiC interface (left inset in Figure 15) [40,95,96]. Because of this strong coupling with the substrate, a buffer layer does not show graphene-like π bands and is electronically inactive [97].…”
Section: Growth Of Graphene On Si Facementioning
confidence: 99%
See 1 more Smart Citation
“…It is known as the buffer layer or zero-layer graphene [25,40,89,[92][93][94]. This reconstructed surface loses its distinct graphene electronic properties because of sp 3 hybridization of about 30% of the carbon atoms which are covalently bonded with the Si atoms of the SiC interface (left inset in Figure 15) [40,95,96]. Because of this strong coupling with the substrate, a buffer layer does not show graphene-like π bands and is electronically inactive [97].…”
Section: Growth Of Graphene On Si Facementioning
confidence: 99%
“…Our results also indicate that there exists a range of optimal terrace width which should be kept in order to maintain formation of one monolayer graphene and to avoid the increase of carrier concentration [73]. The relationships between surface reconstruction, graphene layer thickness, and electronic properties of epitaxial graphene grown on both polar faces of 3C-SiC were studied by using large-area µ-SE mapping ( Figure 41) and LEEM/µ-LEED investigations [95]. Large homogeneous ML graphene domains with sizes up to "2ˆ2 mm 2 on the Si face are observed, while on the C face, domains with homogeneous thickness are significantly smaller.…”
Section: Epitaxial Graphene On 3c-sic and Comparison With Other Polytmentioning
confidence: 99%
“…Such control has been widely achieved for graphene grown on the Si face of SiC, where single-crystalline, homogeneous, and continuous monolayers can cover entire areas from the micro-to the milliscale [1][2][3][4]. On the other hand, even under similar growth conditions, graphitization over the C face of SiC is still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the works employing either 3C-SiC substrates or 3C-SiC templates on Si(111) for the growth of graphene focused on Si-face material. [8][9][10][11][12] Only two works on C-face graphene grown on 3C-SiC(111) by low-10 and high-temperature 11 sublimation in a ultra-high vacuum and an argon atmosphere, respectively, have been published. Both studies reported that C-face graphene grows without the formation of a buffer layer in similarity to the situation for FLG on 4H-and 6H-SiC.…”
mentioning
confidence: 99%
“…The regions with uniform thickness in our sample are considerably larger, of the order of few microns, compared to C-face graphene on 3C-SiC reported previously. 11 A representative LEEM image taken from an area consisting predominantly of 4ML regions is shown in Fig. 4(a).…”
mentioning
confidence: 99%